Identification of iceberg-forming ice quakes from seismic and infrasound data - Yu. A. Vinogradov; A. V. Fedorov; S. V. Baranov; V. E. Asming; I. S. Fedorov (Лëд и снег, 2021)
The application of a joint method of recording seismic and infrasound signals generated during ice calving from the terminal part of the outlet glaciers to identify the process of iceberg formation is considered. For many years, the Kola Branch of the Geophysical Service of the Russian Academy of Sciences has been developing technology for remote monitoring of the processes of destruction of ice sheets in the Arctic. To improve the methodology of geophysical monitoring of processes of the iceberg calving in the Arctic seas in the Svalbard archipelago, the experiment was conducted for the first time on the complex recording of the destruction of the Nordenskiold glacier using seismometers, infrasound microphones and video cameras. The aim of the experiment was to obtain time-synchronized recordings of seismic, infrasound and video signals produced by calving of the glacier edge. The synchronized recordings obtained as a result of the experiment were used to identify specific attributes that characterize the recordings of iceberg-inducing ice quakes. Results of the experiment showed that the calving events that produce floating icebergs generate seismic and infrasonic signals of a special spectral composition and are characterized by the presence of pronounced bands in the spectral-time representation. The revealed characteristic is a distinguishing evidence of a calving event with the iceberg-inducing potential from other types of ice quakes, such as cracking and movement of the glacier body. The experimental results obtained may be used for development of a system for seismic-infrasound monitoring of processes of the iceberg formation.